2020
DOI: 10.1136/ejhpharm-2019-002111
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of drug interactions in hospitalised elderly patients: a systematic review

Abstract: BackgroundThe prevalence of drug–drug interactions (DDIs) in hospital settings is variable, and elderly patients are considered a high risk population for DDIs. There are no systematic reviews describing the prevalence of DDIs in hospitalised elderly patients.ObjectivesTo assess and summarise the available data on the prevalence of DDIs in hospitalised elderly patients and to describe which drugs, drug classes and drug combinations are most commonly involved in DDIs.Data sourceA systematic electronic literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 51 publications
3
42
1
3
Order By: Relevance
“…The term PIM is defined as medications that have adverse effects and, when used by older adults, may outweigh the clinical advantages of the drug, such as mental and functional decline, adverse drug events, drug interactions, unplanned hospitalization, morbidity, and mortality ( Thomas and Thomas, 2019 ; Xing et al, 2019 ; de Oliveira et al, 2020 ; Weeda et al, 2020 ). Higher-income countries have taken several steps to improve rational prescribing in older adults and have developed evidence-based explicit tools to screen and prevent PIM use in older patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term PIM is defined as medications that have adverse effects and, when used by older adults, may outweigh the clinical advantages of the drug, such as mental and functional decline, adverse drug events, drug interactions, unplanned hospitalization, morbidity, and mortality ( Thomas and Thomas, 2019 ; Xing et al, 2019 ; de Oliveira et al, 2020 ; Weeda et al, 2020 ). Higher-income countries have taken several steps to improve rational prescribing in older adults and have developed evidence-based explicit tools to screen and prevent PIM use in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses on the prevalence of polypharmacy and PIM use in the older population, using data from developed countries ( Kaufmann et al, 2014 ; Muhlack et al, 2017 ; Liew et al, 2019 ; Thomas and Thomas, 2019 ; Xing et al, 2019 ; Davies et al, 2020 ; de Oliveira et al, 2020 ; Liew et al, 2020 ; Mohamed et al, 2020 ; Weeda et al, 2020 ), indicated a rising trend of inappropriate medication use in the current healthcare system. However, differences in the population, healthcare settings, and medication use process may limit the generalizability of these findings in developing countries, including India.…”
Section: Introductionmentioning
confidence: 99%
“…Lower rate of interactions, about 46% and 26% had been seen in other studies [24,25] respectively. The heterogeneity in the results of various studies may reflect differences in the conditions of the included patients and level of care, as well as the various methodology used, especially the software used to identify these DDIs [26].…”
Section: Discussionmentioning
confidence: 99%
“…A drugdrug interaction (DDI) can be described as the effect of one medication being changed (enhanced, diminished, or modified) by the presence of another medication when administered simultaneously or successively [9,10]. DDIs are common, with reported prevalence among hospitalized elderly patients ranging from 8 to 100%, and may compromise patient safety [11]. One of the key components to achieving appropriate drug treatment is the access to the needed information for the involved actors, such as prescribers, pharmacists, and patients [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The management of DDIs is a complex process and it involves risk-benefit assessment of the involved drugs. Clinical Decision Support Systems (CDSSs) in the medication management process are used to improve health care quality and efficiency [7,[10][11][12][13][14][15][16]. A CDSS can support health care professionals, such as physicians and pharmacists, in detecting potential DDIs by linking patient-specific factors and current medications together with a knowledge database.…”
Section: Introductionmentioning
confidence: 99%